Tailoring the Ablative Strategy for Atrial Fibrillation: A State-of-the-Art Review - Zefferino Palamà; Martina Nesti; Antonio Gianluca Robles; Antonio Scarà; Silvio Romano; Elena Cavarretta; Maria Penco; Pietro Delise; Mariano Rillo; Leonardo Calò; Luigi Sciarra (Cardiology Research and Practice)
In spite of technological progress and the improving skills of operators, atrial fibrillation (AF) ablation results appear to date to be at a plateau. In any case, the superiority of ablation over pharmacological therapy in terms of effectiveness, reduction of hospitalizations, and improvement has been well demonstrated in recent randomized trials. Triggers, substrate, and modulating factors (elements of Coumel’s triangle) play different roles in paroxysmal and persistent AF, so induction and perpetuation mechanisms of arrhythmia may be different in each patient. Although effective ablative strategies are available for the treatment of paroxysmal AF triggers and persistent AF substrates, an adequate clinical evaluation of the patient is crucial in order to increase the chances of success. Recognizing triggers allows not only performing an effective ablation but also to avoid unnecessary lesions and at the same time reducing the risk of complications. AF beginning and triggers could be recorded by 12-lead ECG, continuous Holter monitoring, or implantable devices. In case of an unsuccessful noninvasive evaluation, nonpulmonary vein triggers should be investigated with an electrophysiological study. Persistent AF needs more effort to perform an accurate substrate characterization. Among the many methods proposed, recently the use of high-density mapping and multipolar catheters seems of particular benefit in order to clarify the arrhythmia mechanisms. Surgical and hybrid techniques allow to treat regions such as the posterior wall or Bachmann’s bundle, which is fundamental for an ablative strategy that goes beyond just pulmonary vein isolation. Too often, patients are referred to electrophysiology laboratories without adequate preprocedural screening and planning in order to submit them to a standard “ready-made” procedure. The accurate search for triggers in paroxysmal AF and the correct recognition of the link between a possible underlying heart disease and the substrate in persistent AF could allow us to tailor the interventional approach in order to overcome the current plateau, increasing ablative procedure success and minimizing complications.